DESIGNING THE PROCESS OF REMOTE EXCHANGE OF ECG DATA - Jabborov Anvar Mansurjonovich (Web of Journals Publishing, 2023)
To study the properties of cardiosignals and store the data of signals received using the AD8232 ECG module, which is considered important for signal processing, we will consider the cloud technology to ensure database and remote data exchange.
Keywords: EKG, ma’lumot baza, API, JSON, REST, SOAP.